Advanced financial modelling - Albrecher, Hansjörg; Runggaldier, W. J. (Wolfgang J.); Schachermayer, Walter (Radon series on computational and applied mathematics ;, 2009)
Annotation This book is a collection of state-of-the-art surveys on various topics in mathematical finance, with an emphasis on recent modelling and computational approaches. The volume is related to a a ~Special Semester on Stochastics with Emphasis on Financea (TM) that took place from September to December 2008 at the Johann Radon Institute for Computational and Applied Mathematics of the Austrian Academy of Sciences in Linz, Austria.